Pengaruh Beban Pajak, Bonus Mechanism, Dan Tunneling Incentive Terhadap Transfer Pricing Dengan Tax Minimization Sebagai Variabel Moderasi Pada Perusahaan Manufaktur Yang Merupakan Perusahaan Multinasional Yang Terdaftar Di BEI Tahun 2019-2023 - Nurul Atika Sari; Rizki Filhayati Rambe; Syamsul Bahri Arifin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to determine whether the effects of tax rates, bonus mechanisms, tunneling incentives, and tax minimization affect transfer pricing in multinational manufacturing companies listed on the Indonesia Stock Exchange. This study aims to determine whether tax rates, bonus mechanisms, and tunneling incentives affect transfer pricing and whether tax minimization moderates transfer pricing in multinational manufacturing companies listed on the Indonesia Stock Exchange. The population in this study was manufacturing companies listed on the Indonesia Stock Exchange in 2019 to 2023. The sample selection in this study was carried out using a purposive sampling method, which resulted in a sample of 27 companies. The data source in this study was secondary data. The analysis method used was descriptive statistics. The results of the research concluded that the effect of tax rate, bonus mechanism, tunneling incentive and tax minimization affect transfer pricing and tax minimization significantly moderates the effect of tax rate on transfer pricing while tax minimization does not significantly moderate the impact of bonus mechanism and tunneling incentive that all independent variables have a significant effect on transfer pricing in manufacturing companies which are multinational companies listed on the Indonesia Stock Exchange.